Pengaruh Karakteristik Bank dan Karakteristik Pasar Terhadap Kemungkinan Terjadinya Merger dan Akuisisi Pada Perbankan di Indonesia - Susy Muchtar; Karima Rahmania (Jurnal Manajemen dan Pemasaran Jasa, 2009)
The purpose of this research is to examine the effect of bank's characteristics and market characteristicstoward the probability of merger and acquisition in Indonesian Banking. The type of data used in this research is secondary data which is collected from Indonesia Stock Exchange and CD Room of Trisakti University. The Sample examined in this research consist of 22 listed commercial banks, which 9 of it have been acquired between 2003 and 2007 using purposive/judgmental sampling as its sample selection technique. This research used Binary Logistic Regression as analysis tool to test the hypothesis in this paper.Findings of this research indicate that three of bank's characteristics, those are bank's size, market share, and bank's growth have a significant effect toward the probability of merger and acquisition. Another bank's characteristics like profit, cost efficiency, capital strength, Liquidity, number of branches do not seem to have effect toward the probability of merger and acquisition. This research also finds that market characteristics those are market concentration, market profitability, and market growth have no effect toward the probability of merger and acquisition.Keywords : Acquisition, Banks, Bank's Characteristics, Market Characteristics, Mergers